A new notebook flexible printed circuit board and backlight module prepared based on a weldable low-temperature silver paste

By using solderable low-temperature silver paste, the problems of high-temperature curing damaging the substrate and poor solderability in the manufacturing of flexible printed circuit boards have been solved. This has enabled high-precision pattern preparation and high-performance chip integration at low temperatures, improving manufacturing efficiency and product reliability.

CN121174379BActive Publication Date: 2026-05-15NANO TOP ELECTRONICS TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511320350.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2026-05-15
Estimated Expiration
2045-09-16

AI Technical Summary

Technical Problem

Existing flexible printed circuit board manufacturing processes suffer from problems such as high-temperature curing damage to the substrate, poor solderability, insufficient flexibility, and easy agglomeration of nanofillers, making it difficult to meet the requirements of high reliability, high integration, and low-cost manufacturing.

Method used

Weldable low-temperature silver paste is used, which contains a specific ratio of conductive fillers, resin system and modified nanofillers. It forms a tough three-dimensional network structure through low-temperature curing, thereby improving conductivity, welding reliability and bending resistance.

Benefits of technology

Achieving high-precision pattern fabrication and high-performance chip integration at low temperatures improves manufacturing efficiency and product reliability. It solves the problems of substrate damage from high-temperature silver paste and agglomeration of nanofillers, and provides excellent mechanical durability and solderability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005598303530000211
    Figure BDA0005598303530000211
  • Figure BDA0005598303530000221
    Figure BDA0005598303530000221
Patent Text Reader

Abstract

The application discloses a novel notebook flexible printed circuit board and a backlight module prepared based on weldable low-temperature silver paste, and belongs to the technical field of electronic materials and devices. A conductor pattern of the flexible printed circuit board comprises a main circuit pattern formed by calendered copper and an auxiliary functional structure formed by weldable low-temperature silver paste in a local area of the main circuit pattern. The solidification temperature of the weldable low-temperature silver paste is 130 DEG C to 145 DEG C, and the silver paste comprises conductive fillers, a polymer resin system, an ester solvent, a curing agent, a silane coupling agent, a polyamide wax thixotropic agent, a polysiloxane defoaming agent, modified carbon nanotubes and modified antimony tin oxide powder. The conductive fillers comprise flaky silver powder, spherical silver powder and low-temperature alloy powder. The low-temperature alloy powder is Sn42Bi58 low-temperature alloy powder with a D50 of 12 mu m to 15 mu m. The application integrates low-temperature solidification, high flexibility, excellent conductivity and direct weldability, and provides a solution suitable for local repair of the flexible printed circuit board, jumper wiring and direct mounting of Mini LED chips.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic materials and devices, and in particular to a novel flexible printed circuit board and backlight module for notebook computers based on solderable low-temperature silver paste. Background Technology

[0002] Flexible printed circuit boards (PCBs), with their significant advantages of light weight, thinness, and bendability, have revolutionized electronic interconnection technology and have become an indispensable core component of modern electronic products such as ultra-thin laptops. Traditional laptop PCBs typically use rolled copper foil to create conductor patterns through processes such as photolithography and etching. This technology is mature and reliable, providing excellent mechanical strength and conductivity. However, with the rapid development of electronic products towards miniaturization and high integration, the design of flexible PCBs is becoming increasingly complex. During manufacturing and repair, it is inevitable to encounter needs such as circuit repair, design changes, jumper wires, or the addition of special functional pads such as test points and grounding pads. However, traditional rolled copper processes have drawbacks in such small-scale modifications. For example, the repair process is cumbersome, requiring re-coating of dry film, exposure, development, and etching, and demanding extremely high operational precision. Adding jumper wires often requires additional soldering steps, introducing new thermal stress and potential failure points. To address these challenges, conductive silver paste, due to its ease of direct printing, has been chosen as an ideal supplementary process.

[0003] Existing conductive silver pastes are mostly based on epoxy resin systems and filled with a high proportion of silver powder to ensure conductivity. However, when these general-purpose silver pastes are applied to the precision manufacturing of notebook FPCs, a series of problems often emerge.

[0004] The primary issue is the mismatch in curing temperatures. To achieve a full cross-linking reaction and obtain optimal mechanical and electrical properties, most high-performance conductive silver pastes are cured at temperatures above 160°C, sometimes even reaching 200°C. However, the glass transition temperature of the flexible substrates commonly used in notebook flexible printed circuit boards (such as polyimide PI) is typically within this range. Prolonged high-temperature baking can cause the flexible substrate to yellow, become brittle, warp, and even delaminate, severely damaging the reliability and lifespan of the flexible printed circuit board.

[0005] In addition, existing conductive silver pastes generally have poor solderability. Although they are conductive, their surfaces are usually not well wetted by conventional tin-lead or lead-free solders, making them unsuitable for direct use as solder pads. If components need to be soldered, they must be pre-plated with gold or tin, which undoubtedly increases the complexity and cost of the process. Especially in advanced applications such as Mini LED backlight modules, a large number of tiny LED chips need to be directly mounted on flexible printed circuit boards, which places extremely high demands on the flatness, solderability, and solder strength of the solder pads, requirements that existing silver pastes cannot meet.

[0006] Existing silver pastes, when used for fine circuitry on flexible printed circuit boards, suffer from problems such as insufficient adhesion to flexible substrates, poor bending resistance, and unsuitable rheological properties for high-precision printing. Factors such as the dispersion stability of fillers in the silver paste, its density after curing, and internal stress directly affect the performance of the circuitry. Although some studies have attempted to improve performance by adding nanomaterials (such as carbon nanotubes and nano-oxides), these nanofillers are prone to agglomeration. If stable and uniform dispersion cannot be achieved in the resin system, they not only fail to provide reinforcement but also become defect centers, leading to decreased conductivity and deteriorated mechanical properties.

[0007] Therefore, there is an urgent need to develop a special conductive silver paste for flexible printed circuit boards (PCBs) in notebooks that can cure rapidly at temperatures below the substrate's tolerance limit, while possessing superior conductivity, strong adhesion to the substrate, and excellent bending resistance. Furthermore, the cured surface must be directly solderable to enable rapid repair, jumper wire fabrication, and high-quality pad manufacturing of PCBs, thus meeting the demands of electronic products for high reliability, high integration, and low-cost manufacturing of PCBs. Summary of the Invention

[0008] The purpose of this invention is to provide a novel flexible printed circuit board and backlight module for notebook computers based on solderable low-temperature silver paste. In order to achieve rapid fabrication of high-precision patterns and direct integration of high-performance chips at low temperatures, this invention addresses the problems existing in the prior art and overcomes the technical bottlenecks in the manufacturing of flexible printed circuit boards, such as high-temperature silver paste damaging the substrate, inability to be directly soldered, poor flexibility of general silver paste, and easy agglomeration of nanofillers. Ultimately, this invention significantly improves the manufacturing efficiency, product yield, and reliability of end applications of flexible printed circuit boards.

[0009] To achieve the above objectives, the present invention provides the following solution:

[0010] This invention provides a flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, comprising a flexible insulating substrate and a conductor pattern disposed on the substrate. The key feature is that the conductor pattern includes a main circuit pattern formed by rolled copper and an auxiliary functional structure formed by solderable low-temperature silver paste in a local area of ​​the main circuit pattern; the auxiliary functional structure includes at least one of a local repair area, a jumper area, and a special pad area.

[0011] The curing temperature of the above-mentioned solderable low-temperature silver paste is 130℃~145℃; by mass parts, the above-mentioned solderable low-temperature silver paste contains 55.1 parts to 75 parts of conductive filler, 10 parts to 20 parts of polymer resin system, 20 parts to 35 parts of ester solvent, 3 parts to 8 parts of curing agent, 1 part to 3 parts of silane coupling agent, 0.5 parts to 2 parts of polyamide wax thixotropic agent, 0.2 parts to 0.5 parts of polysiloxane defoamer, 0.5 parts to 2 parts of modified carbon nanotubes and 0.5 parts to 2 parts of modified antimony tin oxide powder;

[0012] The conductive filler includes flake silver powder with a D50 range of 2.0μm to 5.0μm, spherical silver powder with a D50 range of 0.5μm to 0.8μm, and low-temperature alloy powder, wherein the low-temperature alloy powder has a D50 range of 12μm to 15μm.

[0013] Specifically, the mass ratio of flake silver powder, spherical silver powder, and low-temperature alloy powder in the above-mentioned conductive filler is (1.5~2.5):1:(0.2~0.5); the tap density of the above-mentioned flake silver powder is ≥4.0 g / cm³. 3 The aforementioned low-temperature alloy powder is Sn42Bi58; the specific surface area of ​​the aforementioned spherical silver powder is 1.0 m². 2 / g~2.5m 2 / g.

[0014] Specifically, the aforementioned polymer resin system comprises cashew nut shell epoxy resin, hydrogenated bisphenol A epoxy resin, and carboxyl-terminated liquid nitrile rubber in a mass ratio of 1:(0.8–1.2):(0.3–0.6); the cashew nut shell epoxy resin has an epoxy value of 0.45 eq / 100g–0.55 eq / 100g and a viscosity of 10000 mPa·s–20000 mPa·s at 25°C; the carboxyl-terminated liquid nitrile rubber has a carboxyl mass fraction of 0.4%–0.6% and a number average molecular weight of 3000 Da–5000 Da.

[0015] Preferably, the curing agent is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of (5-7):1, wherein the imidazole accelerator is selected from any one of 2-methylimidazole, 2-ethyl-4-methylimidazole or 1-cyanoethyl-2-phenylimidazole; and the polyether polyamine curing agent is selected from linear polyether diamine.

[0016] Preferably, the silane coupling agent is γ-glycidoxypropyltrimethoxysilane, abbreviated as KH-560; the polysiloxane defoamer is a non-silicone defoamer containing defoaming polysiloxane; and the ester solvent is selected from any one of diethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, or butyl butyrate.

[0017] Furthermore, the aforementioned polyamide wax thixotropic agent is a polyamide wax formed by the condensation of plant fatty acids, dimer fatty acids, and ethylenediamine. Before use, the aforementioned polyamide wax thixotropic agent needs to be activated. The specific operation of the activation treatment is as follows: add the polyamide wax to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:1.5 to 2.0, add aminopropanol, control the activation temperature at 40℃ to 50℃, the stirring speed at 100 r / min to 150 r / min, and activate for 15 min to 30 min; wherein, the mass ratio of polyamide wax, mixed solvent, and aminopropanol is 1:(5 to 8):(0.05 to 0.1).

[0018] Furthermore, the preparation process of the above-mentioned modified carbon nanotubes, in parts by mass, is as follows:

[0019] A1. Acidification treatment: 15 parts of carbon nanotubes are added to a mixed acid consisting of 280-320 parts of concentrated nitric acid and 100-150 parts of concentrated sulfuric acid. 1%-5% of ferric nitrate nonahydrate by mass of carbon nanotubes is added. The mixture is refluxed at 105℃-115℃ for 4-8 hours. After cooling, the mixture is filtered, washed with deionized water until neutral, and dried to obtain carboxylated carbon nanotubes to be cleaned.

[0020] A2. Cleaning of carboxylated carbon nanotubes: The obtained carboxylated carbon nanotubes to be cleaned are dispersed in a nitric acid solution with a concentration of 0.1 mol / L to 0.5 mol / L, and ultrasonically treated at 200 W to 40 W at 40℃ to 60℃ for 20 min to 40 min; filtered, washed with deionized water until the conductivity of the filtrate decreases by <10 μS / cm, and dried to obtain carboxylated carbon nanotubes;

[0021] A3. Silanization modification: Take 10 parts of the above carboxylated carbon nanotubes and disperse them in a mixed solution of 120 to 180 parts of ethanol and water, with a volume ratio of ethanol to water of 1:(0.8 to 1.2). Add 1 to 3 parts of KH-560 and stir ultrasonically at 68℃ to 72℃ for 5 to 7 hours. After the reaction, filter, wash, and dry to obtain silanized modified carbon nanotubes. The ultrasonic power is 200W to 400W, and the stirring speed during the ultrasonic process is 300r / min to 500r / min.

[0022] A4. Supercritical treatment: Take 5 parts of the above-mentioned silanized modified carbon nanotubes, 120-180 parts of deionized water, and 13-18 parts of cocamidopropyl dimethylamine acetone and add them to a supercritical reactor. After sealing, introduce carbon dioxide to a pressure of 28-32 MPa and react at a temperature of 73-78°C for 5-7 hours. After depressurization, add 3-8 parts of dodecyl dimethyl benzyl ammonium chloride, inject carbon dioxide to a pressure of 48-52 MPa, and stir at a speed of 200-400 r / min for 3-5 hours.

[0023] A5. After depressurization, the modified carbon nanotubes are separated, washed, and dried to obtain the above-mentioned modified carbon nanotubes.

[0024] Furthermore, the preparation process of the above-mentioned modified antimony tin oxide powder, in parts by mass, is as follows:

[0025] B1. Disperse 10 parts of antimony tin oxide powder with an average particle size of 30nm to 70nm in 100 parts to 120 parts of anhydrous ethanol, and sonicate at 200W to 40W for 20min to 40min to obtain a suspension.

[0026] B2. Add 1 to 2 parts of KH-560 and 0.2 to 0.8 parts of acetic acid to the suspension as a catalyst, and stir the reaction at 55°C to 65°C for 3 to 5 hours.

[0027] B3. After the reaction is completed, the mixture is centrifuged, washed, dried and ground, and then passed through a 500-800 mesh sieve to obtain the above-mentioned modified antimony tin oxide powder.

[0028] Furthermore, the preparation method of the above-mentioned solderable low-temperature silver paste is as follows:

[0029] S1. Add ester solvent to the reaction vessel, then add polymer resin system, stir at 60℃~80℃ until the resin dissolves, add silane coupling agent and polysiloxane defoamer, cool to room temperature, add curing agent, keep the solution temperature at 22℃~30℃, stir until all phases are completely dissolved and mixed to obtain carrier solution.

[0030] S2. Add polyamide wax thixotropic agent to the above carrier solution and stir and mix at room temperature to obtain mixed solution A;

[0031] S3. Add low-temperature alloy powder to mixed solution A and stir at room temperature to obtain mixed solution B;

[0032] S4. Add the flake silver powder and spherical silver powder to the mixed solution B, and stir at room temperature to obtain the mixed solution C;

[0033] S5. Add the modified carbon nanotubes and modified antimony tin oxide powder to the mixed solution C, stir and mix, and control the stirring temperature to not exceed 30℃ to obtain the mixed solution D;

[0034] S6. Transfer the mixed solution D to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 65μm-75μm and the gap between the middle roller and the slow roller to 25μm-35μm, and grind for 1-2 passes. Then, adjust the gap between the fast roller and the middle roller to 35μm-45μm and the gap between the middle roller and the slow roller to 5-15μm, and grind for another 1-2 passes. Grind for a total of 2-4 passes to obtain the ground silver paste.

[0035] S7. Transfer the ground silver paste to a vacuum stirring vessel and stir and mix it under a vacuum of ≤-0.095MPa. After stirring, encapsulate the silver paste to obtain the above-mentioned solderable low-temperature silver paste.

[0036] A backlight module based on solderable low-temperature silver paste includes the aforementioned flexible printed circuit board for laptops based on solderable low-temperature silver paste, and a Mini LED chip soldered to a conductor pattern on the aforementioned flexible printed circuit board for laptops using low-temperature solder; the Mini LED chip is soldered to a pad area formed by the aforementioned solderable low-temperature silver paste in the aforementioned conductor pattern.

[0037] The present invention discloses the following technical effects:

[0038] The solderable low-temperature silver paste and its application in flexible printed circuit boards and backlight modules provided by this invention achieve a comprehensive improvement in mechanical properties, electrical conductivity, and solderability under low-temperature curing conditions through the synergistic effect of its components. It has the following beneficial effects:

[0039] First, the silver paste of the present invention exhibits excellent mechanical durability. This is because the composite resin system composed of cashew phenol-based epoxy resin, hydrogenated bisphenol A epoxy resin, and carboxyl-terminated liquid nitrile rubber in a specific ratio of the present invention can form a strong and tough three-dimensional network structure after curing, thereby giving the cured film a stable adhesion and excellent bending resistance to the polyimide substrate, fully meeting the stringent reliability requirements of flexible electronic devices.

[0040] Secondly, the silver paste of the present invention possesses high conductivity and stable solderability. The conductive filler of the present invention contains flake and spherical silver powder of specific particle sizes, which together form a highly efficient conductive network. Meanwhile, the Sn42Bi58 low-temperature alloy powder with a D50 in the range of 12μm to 15μm melts and flows during the solidification process, not only participating in the formation of conductive pathways, but also forming active sites on the surface of the silver paste that can be wetted by solder, achieving a strong metallurgical bond with the low-temperature solder, so that the silver paste pattern can be directly used as a high-reliability solder pad.

[0041] Third, the introduction of the modified filler in this invention has a synergistic reinforcing effect. Silanized and supercritical carbon nanotubes enhance the mechanical strength and electrical conductivity of the coating, while modified antimony tin oxide nanoparticles help optimize contact resistance and improve system stability. The combined use of these two materials achieves good dispersion of the nanophase without the addition of additional dispersants, avoiding the negative impacts of traditional dispersants on conductivity and weldability.

[0042] Fourth, this invention integrates low-temperature curing (≤145℃), high flexibility, excellent conductivity, and direct solderability into one, providing a comprehensive solution suitable for local repair of flexible printed circuit boards, jumper wires, and direct mounting of Mini LED chips. It effectively solves the problems of process complexity and reliability caused by high-temperature curing damaging the substrate, the need for pre-plating for welding, and insufficient flexibility in the prior art. Detailed Implementation

[0043] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0044] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0045] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0046] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0047] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0048] Example 1

[0049] This embodiment provides a flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, including a flexible insulating substrate and a conductor pattern disposed on the substrate. The conductor pattern includes a main circuit pattern formed from rolled copper, and auxiliary functional structures formed by a solderable low-temperature silver paste sample 1 in a local area of ​​the main circuit pattern; the auxiliary functional structures in this embodiment include local repair areas, jumper areas, and special pad areas.

[0050] By mass, the solderable low-temperature silver paste sample 1 of this embodiment comprises: 60.1 parts of conductive filler sample 1, 15 parts of polymer resin system sample 1, 28 parts of diethylene glycol butyl ether acetate, 5 parts of curing agent sample 1, 2 parts of silane coupling agent KH-560, 1 part of polyamide wax thixotropic agent sample 1, 0.3 parts of polysiloxane defoamer BYK-055, 1 part of modified carbon nanotube sample 1, and 1 part of modified antimony tin oxide powder sample 1.

[0051] Conductive filler sample 1 comprises: a 3.5 μm flake silver powder sample 1, a 0.6 μm spherical silver powder sample 1, and a 13 μm Sn42Bi58 (representing 42% tin and 58% bismuth) low-temperature alloy powder sample 1; wherein the mass ratio of the flake silver powder sample 1, the spherical silver powder sample 1, and the low-temperature alloy powder sample 1 is 2:1:0.3; the tap density of the flake silver powder sample 1 is 4.6 g / cm³. 3 The specific surface area of ​​spherical silver powder sample 1 is 2.1 m². 2 / g;

[0052] The polymer resin system sample 1 includes cashew nut shell phenolic epoxy resin sample 1, hydrogenated bisphenol A epoxy resin and carboxyl-terminated liquid nitrile rubber sample 1 with a mass ratio of 1:1:0.4; wherein, the cashew nut shell phenolic epoxy resin sample 1 has an epoxy value of 0.50 eq / 100g and a viscosity of 15000 mPa·s at 25℃; the carboxyl-terminated liquid nitrile rubber sample 1 has a carboxyl group mass fraction of 0.51% and a number average molecular weight of 4000 Da.

[0053] Curing agent sample 1 is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of 6:1. The imidazole accelerator is a latent imidazole accelerator, specifically 2-methylimidazole; the polyether polyamine curing agent is a linear polyether diamine, specifically EDR-148.

[0054] The polyamide wax thixotropic agent sample 1 is a polyamide wax sample 1 composed of plant fatty acids, dimer fatty acids and ethylenediamine, specifically PA-8800. Before use, PA-8800 needs to be activated. The specific activation procedure is as follows: add PA-8800 to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:1.8, add aminopropanol, control the activation temperature at 45℃, the stirring speed at 120r / min, and activate for 20min; wherein, the mass ratio of PA-8800, mixed solvent and aminopropanol is 1:6:0.08.

[0055] The preparation process of modified carbon nanotube sample 1, by mass parts, is as follows:

[0056] A1. Acidification treatment: 15 parts of carbon nanotubes were added to a mixed acid consisting of 300 parts of concentrated nitric acid and 120 parts of concentrated sulfuric acid. 3% of the carbon nanotubes were added to ferric nitrate nonahydrate. The mixture was refluxed at 110°C for 6 hours. After cooling, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 90°C for 18 hours to obtain the carboxylated carbon nanotube sample 1 to be cleaned.

[0057] A2. Cleaning carboxylated carbon nanotubes: Disperse the carboxylated carbon nanotube sample 1 to be cleaned in a 0.3 mol / L nitric acid solution and sonicate it at 50℃ and 300W for 30 min; filter, wash with deionized water until the conductivity of the filtrate decreases by <10 μS / cm, and dry to obtain carboxylated carbon nanotube sample 1.

[0058] A3. Silanization modification: Take 10 parts of carboxylated carbon nanotube sample 1 and disperse it in a mixed solution of 160 parts of ethanol and water with a volume ratio of ethanol to water of 1:1.0. Add 2 parts of KH-560 and react with ultrasonication at 300W power and stirring at 400r / min at 70℃ for 6h. After the reaction is completed, filter, wash 3 times with anhydrous ethanol, and dry to obtain silanized modified carbon nanotube sample 1.

[0059] A4. Supercritical treatment: Take 5 parts of silanized modified carbon nanotube sample 1, 150 parts of deionized water, and 15 parts of cocamidopropyl dimethylamine acetone and add them to a supercritical reactor. After sealing, introduce carbon dioxide to a pressure of 30 MPa and react at 75°C for 6 hours. After depressurization, add 5 parts of dodecyl dimethyl benzyl ammonium chloride, inject carbon dioxide to a pressure of 50 MPa, and stir at 300 r / min for 4 hours.

[0060] A5. After depressurization and separation, the sample was washed with deionized water and dried under vacuum at 90℃ for 8 hours to obtain modified carbon nanotube sample 1.

[0061] The preparation process of modified antimony tin oxide powder sample 1, by mass parts, is as follows:

[0062] B1. Disperse 10 parts of antimony tin oxide powder with an average particle size of 50 nm in 110 parts of anhydrous ethanol, and sonicate at 300 W for 30 min to obtain a suspension.

[0063] B2. Add 1.5 parts of KH-560 and 0.5 parts of acetic acid to the suspension as catalysts, and stir the mixture at 400 r / min at 60°C for 4 h.

[0064] B3. After the reaction was completed, the mixture was centrifuged, washed four times with anhydrous ethanol, dried under vacuum at 80°C for 12 hours, ground, and passed through a 600-mesh sieve to obtain modified antimony tin oxide powder sample 1.

[0065] Using the above-mentioned raw materials, a solderable low-temperature silver paste sample 1 was prepared, specifically as follows:

[0066] S1. Add 28 parts of diethylene glycol butyl ether acetate to the reactor, then add 15 parts of polymer resin system sample 1. Stir at 70°C and 400 r / min for 30 min until the resin is completely dissolved. Add 2 parts of silane coupling agent KH-560 and 0.3 parts of polysiloxane defoamer BYK-055. Cool to room temperature, add 5 parts of curing agent sample 1, keep the solution temperature at 25°C, and stir until all phases are completely dissolved and mixed to obtain carrier solution 1.

[0067] S2. Add 1 part of activated polyamide wax thixotropic agent sample 1 to carrier solution 1, and stir at 500 r / min for 45 min at room temperature to obtain mixed solution A1.

[0068] S3. Add 5.5 parts of Sn42Bi58 low-temperature alloy powder sample 1 to the mixed solution A1, and stir at 500 r / min for 45 min at room temperature to obtain mixed solution B1.

[0069] S4. Add 36.4 parts of flake silver powder sample 1 and 18.2 parts of spherical silver powder sample 1 to the mixed solution B1, and stir at 1000 r / min for 80 min at room temperature to obtain mixed solution C1.

[0070] S5. Add 1 part of modified carbon nanotube sample 1 and 1 part of modified antimony tin oxide powder sample 1 to the mixed solution C1, stir at 1200 r / min for 110 min, and control the stirring temperature at 25℃ to obtain mixed solution D1.

[0071] S6. Transfer the mixed solution D1 to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 70 μm and the gap between the middle roller and the slow roller to 30 μm and grind twice. Then, adjust the gap between the fast roller and the middle roller to 40 μm and the gap between the middle roller and the slow roller to 10 μm and grind once more. Grind a total of 3 times to obtain the ground silver paste sample 1.

[0072] S7. Transfer the ground silver paste sample 1 to a vacuum mixing vessel and stir at a speed of 40 r / min for 30 min under a vacuum of -0.100 MPa. After stirring, encapsulate the silver paste to obtain solderable low-temperature silver paste sample 1. The curing temperature of solderable low-temperature silver paste sample 1 is 135℃.

[0073] Example 2

[0074] This embodiment provides a flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, including a flexible insulating substrate and a conductor pattern disposed on the substrate. The conductor pattern includes a main circuit pattern formed from rolled copper, and auxiliary functional structures formed by a solderable low-temperature silver paste sample 2 in a local area of ​​the main circuit pattern; in this embodiment, the auxiliary functional structures include local repair areas and jumper areas.

[0075] By mass, the solderable low-temperature silver paste sample 2 of this embodiment comprises: 75 parts conductive filler sample 2, 10 parts polymer resin system sample 2, 20 parts ethylene glycol ethyl ether acetate, 8 parts curing agent sample 2, 1 part silane coupling agent KH-560, 0.5 parts polyamide wax thixotropic agent sample 2, 0.2 parts polysiloxane defoamer BYK-088, 0.5 parts modified carbon nanotube sample 2, and 2 parts modified antimony tin oxide powder sample 2.

[0076] Conductive filler sample 2 comprises: a 5.0 μm flake silver powder sample 2, a 0.5 μm spherical silver powder sample 2, and a 12 μm Sn42Bi58 cryogenic alloy powder sample 2; wherein the mass ratio of the flake silver powder sample 2, the spherical silver powder sample 2, and the cryogenic alloy powder sample 2 is 1.5:1:0.5; the tap density of the flake silver powder sample 2 is 4.0 g / cm³. 3 The specific surface area of ​​spherical silver powder sample 2 is 1.0 m². 2 / g;

[0077] The polymer resin system sample 2 includes cashew nut shell phenolic epoxy resin sample 2, hydrogenated bisphenol A epoxy resin and carboxyl-terminated liquid nitrile rubber sample 2 with a mass ratio of 1:0.8:0.6; wherein, the cashew nut shell phenolic epoxy resin sample 2 has an epoxy value of 0.45 eq / 100g and a viscosity of 20000 mPa·s at 25℃; the carboxyl-terminated liquid nitrile rubber sample 2 has a carboxyl mass fraction of 0.6% and a number average molecular weight of 5000 Da.

[0078] Curing agent sample 2 is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of 7:1. The imidazole accelerator is 2-methylimidazole; the polyether polyamine curing agent is EDR-148.

[0079] Polyamide wax thixotropic agent sample 2 is a polyamide wax sample 2 composed of plant fatty acids, dimer fatty acids and ethylenediamine, specifically MT 6650. Before use, MT 6650 needs to be activated. The specific activation procedure is as follows: add MT 6650 to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:1.5, add aminopropanol, control the activation temperature at 50℃, the stirring speed at 100 r / min, and activate for 30 min; wherein, the mass ratio of MT 6650, mixed solvent and aminopropanol is 1:8:0.05.

[0080] The preparation process of modified carbon nanotube sample 2, by mass parts, is as follows:

[0081] A1. Acidification treatment: 15 parts of carbon nanotubes were added to a mixed acid consisting of 320 parts of concentrated nitric acid and 100 parts of concentrated sulfuric acid. 5% of the carbon nanotubes were added to ferric nitrate nonahydrate. The mixture was refluxed at 115°C for 4 hours. After cooling, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 100°C for 12 hours to obtain carboxylated carbon nanotube sample 2 to be cleaned.

[0082] A2. Cleaning carboxylated carbon nanotubes: Disperse the carboxylated carbon nanotube sample 2 to be cleaned in a 0.1 mol / L nitric acid solution and sonicate it at 400 W at 40℃ for 20 min; filter, wash with deionized water until the conductivity of the filtrate decreases by <10 μS / cm, and dry to obtain carboxylated carbon nanotube sample 2.

[0083] A3. Silanization modification: Take 10 parts of carboxylated carbon nanotube sample 2 and disperse it in a mixed solution of 120 parts of ethanol and water with a volume ratio of ethanol to water of 1:1.2. Add 3 parts of KH-560 and react with ultrasonication at 400W power and stirring at 300r / min at 72℃ for 5h. After the reaction is completed, filter, wash 4 times with anhydrous ethanol, and dry to obtain silanized modified carbon nanotube sample 2.

[0084] A4. Supercritical treatment: Take 5 parts of silanized modified carbon nanotube sample, 180 parts of deionized water, and 13 parts of cocamidopropyl dimethylamine acetone and add them to a supercritical reactor. After sealing, introduce carbon dioxide to a pressure of 32 MPa and react at 73°C for 7 hours. After depressurization, add 8 parts of dodecyl dimethyl benzyl ammonium chloride and inject carbon dioxide to a pressure of 52 MPa. Stir at 200 r / min for 3 hours.

[0085] A5. After depressurization and separation, the sample was washed with deionized water and dried under vacuum at 100℃ for 6 hours to obtain modified carbon nanotube sample 2.

[0086] The preparation process of modified antimony tin oxide powder sample 2, by mass parts, is as follows:

[0087] B1. Disperse 10 parts of antimony tin oxide powder with an average particle size of 70 nm in 120 parts of anhydrous ethanol, and sonicate at 400 W for 20 min to obtain a suspension.

[0088] B2. Add 2 parts of KH-560 and 0.8 parts of acetic acid to the suspension as catalyst, and stir the mixture at 300 r / min at 55°C for 3 h.

[0089] B3. After the reaction was completed, the mixture was centrifuged, washed three times with anhydrous ethanol, dried under vacuum at 90°C for 8 hours, ground, and passed through an 800-mesh sieve to obtain modified antimony tin oxide powder sample 2.

[0090] Using the above-mentioned raw materials and in the specified proportions, solderable low-temperature silver paste sample 2 was prepared, specifically as follows:

[0091] S1. Add 20 parts of ethylene glycol ethyl ether acetate to the reactor, then add 10 parts of polymer resin system sample 2. Stir at 60°C and 300 r / min for 40 min until the resin is completely dissolved. Add 1 part of silane coupling agent KH-560 and 0.2 parts of polysiloxane defoamer BYK-088. Cool to room temperature, add 8 parts of curing agent sample 2, keep the solution temperature at 30°C, and stir until all phases are completely dissolved and mixed to obtain carrier solution 2.

[0092] S2. Add 0.5 parts of activated polyamide wax thixotropic agent sample 2 to carrier solution 2, and stir at 600 r / min for 30 min at room temperature to obtain mixed solution A2.

[0093] S3. Add 12.5 parts of Sn42Bi58 low-temperature alloy powder sample 2 to the mixed solution A2, and stir at 600 r / min for 30 min at room temperature to obtain mixed solution B2.

[0094] S4. Add 37.5 parts of flake silver powder sample 2 and 25 parts of spherical silver powder sample 2 to the mixed solution B2, and stir at 1500 r / min for 90 min at room temperature to obtain mixed solution C2.

[0095] S5. Add 0.5 parts of modified carbon nanotube sample 2 and 2 parts of modified antimony tin oxide powder sample 2 to the mixed solution C2, stir at 1500 r / min for 90 min, and control the stirring temperature at 30℃ to obtain mixed solution D2.

[0096] S6. Transfer the mixed solution D2 to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 75 μm and the gap between the middle roller and the slow roller to 25 μm and grind once. Then, adjust the gap between the fast roller and the middle roller to 35 μm and the gap between the middle roller and the slow roller to 5 μm and grind once more. Grind a total of 2 times to obtain the ground silver paste sample 2.

[0097] S7. Transfer the ground silver paste sample 2 to a vacuum mixing vessel and stir at 50 r / min for 20 min under a vacuum of -0.095 MPa. After stirring, encapsulate the silver paste to obtain solderable low-temperature silver paste sample 2. The curing temperature of solderable low-temperature silver paste sample 2 is 130℃.

[0098] Example 3

[0099] This embodiment provides a flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, including a flexible insulating substrate and a conductor pattern disposed on the substrate. The conductor pattern includes a main circuit pattern formed of rolled copper and auxiliary functional structures formed by a solderable low-temperature silver paste sample 3 in a local area of ​​the main circuit pattern; in this embodiment, the auxiliary functional structures include special pad areas.

[0100] By mass, the solderable low-temperature silver paste sample 3 of this embodiment comprises: 55 parts conductive filler sample 3, 20 parts polymer resin system sample 3, 35 parts butyl butyrate, 3 parts curing agent sample 3, 3 parts silane coupling agent KH-560, 2 parts polyamide wax thixotropic agent sample 3, 0.5 parts polysiloxane defoamer TEGO Flow 300, 2 parts modified carbon nanotube sample 3, and 0.5 parts modified antimony tin oxide powder sample 3.

[0101] Conductive filler sample 3 comprises: a sheet-like silver powder sample 3 with a D50 of 2.0 μm, a spherical silver powder sample 3 with a D50 of 0.8 μm, and a Sn42Bi58 cryogenic alloy powder sample 3 with a D50 of 15 μm; wherein the mass ratio of the sheet-like silver powder sample 3, the spherical silver powder sample 3, and the cryogenic alloy powder sample 3 is 2.5:1:0.2; the tap density of the sheet-like silver powder sample 3 is 4.5 g / cm³. 3 The specific surface area of ​​spherical silver powder sample 3 is 2.5 m². 2 / g;

[0102] The polymer resin system sample 3 includes cashew nut shell phenolic epoxy resin sample 3, hydrogenated bisphenol A epoxy resin and carboxyl-terminated liquid nitrile rubber sample 3 with a mass ratio of 1:1.2:0.3; wherein, the cashew nut shell phenolic epoxy resin sample 3 has an epoxy value of 0.55 eq / 100g and a viscosity of 10000 mPa·s at 25℃; the carboxyl-terminated liquid nitrile rubber sample 3 has a carboxyl group mass fraction of 0.4% and a number average molecular weight of 3000 Da.

[0103] Curing agent sample 3 is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of 5:1. The imidazole accelerator is 2-methylimidazole, and the polyether polyamine curing agent is EDR-148.

[0104] Polyamide wax thixotropic agent sample 3 is a polyamide wax sample 3 composed of plant fatty acids, dimer fatty acids and ethylenediamine, specifically thixotropic agent 7500. Before use, thixotropic agent 7500 needs to be activated. The specific activation procedure is as follows: add thixotropic agent 7500 to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:2.0, add aminopropanol, control the activation temperature at 40℃, the stirring speed at 150 r / min, and activate for 15 min; wherein, the mass ratio of thixotropic agent 7500, mixed solvent and aminopropanol is 1:5:0.1.

[0105] The preparation process of modified carbon nanotube sample 3, by mass fraction, is as follows:

[0106] A1. Acidification treatment: 15 parts of carbon nanotubes were added to a mixed acid consisting of 280 parts of concentrated nitric acid and 150 parts of concentrated sulfuric acid. 1% of the carbon nanotubes were added to ferric nitrate nonahydrate. The mixture was refluxed at 105°C for 8 hours. After cooling, the mixture was filtered, washed with deionized water until neutral, and vacuum dried at 80°C for 24 hours to obtain the carboxylated carbon nanotube sample 3 to be cleaned.

[0107] A2. Cleaning carboxylated carbon nanotubes: Disperse the carboxylated carbon nanotube sample 3 to be cleaned in a 0.5 mol / L nitric acid solution and sonicate at 60℃ and 200W power for 40 min; filter, wash with deionized water until the conductivity of the filtrate decreases by <10 μS / cm, dry, and obtain carboxylated carbon nanotube sample 3.

[0108] A3. Silanization modification: Take 10 parts of carboxylated carbon nanotube sample 3 and disperse it in a mixed solution of 180 parts of ethanol and water with a volume ratio of ethanol to water of 1:0.8. Add 1 part of KH-560 and react with ultrasonication at 200W power and stirring at 500r / min at 68℃ for 7h. After the reaction is completed, filter, wash 3 times with anhydrous ethanol, and dry to obtain silanized modified carbon nanotube sample 3.

[0109] A4. Supercritical treatment: Take 5 parts of silanized modified carbon nanotube sample, 120 parts of deionized water, and 18 parts of cocamidopropyl dimethylamine acetone and add them to a supercritical reactor. After sealing, introduce carbon dioxide to a pressure of 28 MPa and react at 78℃ for 5 hours. After depressurization, add 3 parts of dodecyl dimethyl benzyl ammonium chloride, inject carbon dioxide to a pressure of 48 MPa, and stir at 400 r / min for 5 hours.

[0110] A5. After depressurization and separation, the sample was washed with deionized water and vacuum dried at 80℃ for 12 hours to obtain modified carbon nanotube sample 3.

[0111] The preparation process of modified antimony tin oxide powder sample 3, by mass parts, is as follows:

[0112] B1. Disperse 10 parts of antimony tin oxide powder with an average particle size of 30 nm in 100 parts of anhydrous ethanol, and sonicate at 200 W for 40 min to obtain a suspension.

[0113] B2. Add 1 part of KH-560 and 0.2 parts of acetic acid to the suspension as catalyst, and stir at 500 r / min at 65°C for 5 h.

[0114] B3. After the reaction was completed, the mixture was centrifuged, washed four times with anhydrous ethanol, dried under vacuum at 70°C for 16 hours, ground, and passed through a 500-mesh sieve to obtain modified antimony tin oxide powder sample 3.

[0115] Using the above-mentioned raw materials and in the specified proportions, solderable low-temperature silver paste sample 3 was prepared, specifically as follows:

[0116] S1. Add 35 parts of butyl butyrate to the reactor, then add 20 parts of polymer resin system sample 3. Stir at 80℃ and 500r / min for 20min until the resin is completely dissolved. Add 3 parts of silane coupling agent KH-560 and 0.5 parts of polysiloxane defoamer TEGO Flow 300. Cool to room temperature, add 3 parts of curing agent sample 3, keep the solution temperature at 22℃, and stir until all phases are completely dissolved and mixed to obtain carrier solution 3.

[0117] S2. Add 2 parts of activated polyamide wax thixotropic agent sample 3 to carrier solution 3, and mix at room temperature and 400 r / min for 60 min to obtain mixed solution A3.

[0118] S3. Add 3.0 parts of Sn42Bi58 low-temperature alloy powder sample 3 to the mixed solution A3, and stir at 400 r / min for 60 min at room temperature to obtain mixed solution B3;

[0119] S4. Add 37.1 parts of flake silver powder sample 3 and 14.9 parts of spherical silver powder sample 3 to the mixed solution B3, and stir at 1000 r / min for 150 min at room temperature to obtain mixed solution C3.

[0120] S5. Add 2 parts of modified carbon nanotube sample 3 and 0.5 parts of modified antimony tin oxide powder sample 3 to the mixed solution C3, stir at 1000 r / min for 150 min, and control the stirring temperature at 22℃ to obtain mixed solution D3.

[0121] S6. Transfer the mixed solution D3 to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 65 μm and the gap between the middle roller and the slow roller to 35 μm and grind twice. Then, adjust the gap between the fast roller and the middle roller to 25 μm and the gap between the middle roller and the slow roller to 15 μm and grind twice more. Grind a total of 4 times to obtain the ground silver paste sample 3.

[0122] S7. Transfer the ground silver paste sample 3 to a vacuum mixing vessel and stir at 30 r / min for 40 min under a vacuum of -0.102 MPa. After stirring, encapsulate the silver paste to obtain solderable low-temperature silver paste sample 3. The curing temperature of solderable low-temperature silver paste sample 3 is 145℃.

[0123] Example 4

[0124] This embodiment provides a backlight module based on solderable low-temperature silver paste, including a flexible printed circuit board for a notebook computer prepared according to Embodiment 1 based on solderable low-temperature silver paste, and a Mini LED chip soldered to a conductor pattern on the flexible printed circuit board for a notebook computer by low-temperature solder; the Mini LED chip is soldered to a pad area formed by the aforementioned solderable low-temperature silver paste in the conductor pattern.

[0125] Example 5

[0126] This embodiment provides a backlight module based on solderable low-temperature silver paste, including a flexible printed circuit board for a notebook computer prepared according to Embodiment 2 based on solderable low-temperature silver paste, and a Mini LED chip soldered to a conductor pattern on the flexible printed circuit board for a notebook computer by low-temperature solder; the Mini LED chip is soldered to a pad area formed by the aforementioned solderable low-temperature silver paste in the conductor pattern.

[0127] Example 6

[0128] This embodiment provides a backlight module based on solderable low-temperature silver paste, including a flexible printed circuit board for a notebook computer based on solderable low-temperature silver paste prepared in Embodiment 3, and a Mini LED chip soldered to a conductor pattern on the flexible printed circuit board for a notebook computer by low-temperature solder; the Mini LED chip is soldered to a pad area formed by the aforementioned solderable low-temperature silver paste in the conductor pattern.

[0129] Comparative Example 1

[0130] This comparative example provides a flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, including a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed of rolled copper and auxiliary functional structures formed by solderable low-temperature silver paste reference 1 in local areas of the main circuit pattern; the auxiliary functional structures in this comparative example include local repair areas, jumper areas, and special pad areas.

[0131] By mass, the solderable low-temperature silver paste control sample 1 of this comparative example comprises: 60.1 parts conductive filler sample 1, 15 parts polymer resin system control sample 1, 28 parts diethylene glycol butyl ether acetate, 5 parts curing agent sample 1, 2 parts silane coupling agent KH-560, 1 part polyamide wax thixotropic agent sample 1, 0.3 parts polysiloxane defoamer BYK-055, 1 part modified carbon nanotube sample 1, and 1 part modified antimony tin oxide powder sample 1.

[0132] Reference standard 1 for the polymer resin system is a linear phenolic epoxy resin and a hydrogenated bisphenol A type epoxy resin in a mass ratio of 4:1.

[0133] Using the above-mentioned raw materials, a solderable low-temperature silver paste reference standard 1 was prepared. The specific process was the same as in Example 1, except that the polymer resin system sample 1 was replaced with the polymer resin system reference standard 1. The curing temperature of the prepared solderable low-temperature silver paste reference standard 1 was 150°C.

[0134] Comparative Example 2

[0135] This comparative example provides a flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, including a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed of rolled copper and auxiliary functional structures formed by solderable low-temperature silver paste reference 2 in local areas of the main circuit pattern; the auxiliary functional structures in this comparative example include local repair areas, jumper areas, and special pad areas.

[0136] By mass, the solderable low-temperature silver paste reference standard 2 of this comparative example contains: 60.1 parts of conductive filler reference standard 1, 15 parts of polymer resin system sample 1, 28 parts of diethylene glycol butyl ether acetate, 5 parts of curing agent sample 1, 2 parts of silane coupling agent KH-560, 1 part of polyamide wax thixotropic agent sample 1, 0.3 parts of polysiloxane defoamer BYK-055, 1 part of modified carbon nanotube sample 1, and 1 part of modified antimony tin oxide powder sample 1.

[0137] The conductive filler reference standard 1 comprises: a sheet silver powder sample 1 with a D50 of 3.5 μm, a spherical silver powder sample 1 with a D50 of 0.6 μm, and a Sn42Bi58 low-temperature alloy powder reference standard 1 with a D50 of 3 μm; wherein the mass ratio of the sheet silver powder sample 1, the spherical silver powder sample 1, and the low-temperature alloy powder sample 1 is 2:1:0.3.

[0138] Using the above-mentioned raw materials, a solderable low-temperature silver paste reference standard 2 was prepared. The specific process was the same as in Example 1, except that the conductive filler sample 1 was replaced with the conductive filler reference standard 1. The curing temperature of the prepared solderable low-temperature silver paste reference standard 2 was 135°C.

[0139] Comparative Example 3

[0140] This comparative example provides a flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, including a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed of rolled copper, and auxiliary functional structures formed by solderable low-temperature silver paste reference 3 in local areas of the main circuit pattern; the auxiliary functional structures in this comparative example include local repair areas, jumper areas, and special pad areas.

[0141] By mass, the solderable low-temperature silver paste reference standard 3 of this comparative example comprises: 60.1 parts of conductive filler reference standard 1, 15 parts of polymer resin system sample 1, 28 parts of diethylene glycol butyl ether acetate, 5 parts of curing agent sample 1, 2 parts of silane coupling agent KH-560, 1 part of polyamide wax thixotropic agent sample 1, 0.3 parts of polysiloxane defoamer BYK-055, and 2 parts of modified carbon nanotube sample 1.

[0142] Using the above-mentioned raw materials, a solderable low-temperature silver paste reference standard 3 was prepared. The specific process was the same as in Example 1, except that modified antimony tin oxide powder sample 1 was not added in step S5, and the amount of modified carbon nanotube sample 1 added was 2 parts. The curing temperature of the prepared solderable low-temperature silver paste reference standard 3 was 135℃.

[0143] Comparative Example 4

[0144] This comparative example provides a flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, including a flexible insulating substrate and conductor patterns disposed on the substrate. The conductor patterns include a main circuit pattern formed of rolled copper, and auxiliary functional structures formed by solderable low-temperature silver paste reference 4 in local areas of the main circuit pattern; the auxiliary functional structures in this comparative example include local repair areas, jumper areas, and special pad areas.

[0145] By mass, the solderable low-temperature silver paste control sample 4 of this comparative example comprises: 60.1 parts of conductive filler sample 1, 15 parts of polymeric resin system sample 1, 28 parts of diethylene glycol butyl ether acetate, 5 parts of curing agent sample 1, 2 parts of silane coupling agent KH-560, 1 part of polyamide wax thixotropic agent sample 1, 0.3 parts of polysiloxane defoamer BYK-055, 1 part of modified carbon nanotube sample 1, 1 part of modified antimony tin oxide powder sample 1, and 1.5 parts of polymeric dispersant BYK-163.

[0146] Using the above-mentioned raw materials, a solderable low-temperature silver paste reference standard 4 was prepared. The specific process was the same as in Example 1, except that in step S1, 1.5 parts of polymeric dispersant BYK-163 were added along with 2 parts of silane coupling agent KH-560 and 0.3 parts of polysiloxane defoamer BYK-055. The curing temperature of the prepared solderable low-temperature silver paste reference standard 4 was 137℃.

[0147] Analysis and Testing

[0148] Flexible antennas were formed on polyimide (PI) substrates using screen printing equipment for solderable low-temperature silver paste samples 1-3 and solderable low-temperature silver paste controls 1-4. After curing at their respective curing temperatures for 30 minutes, mechanical and electrical properties were tested. The flexible antennas were 10 mm × 70 mm in size, the PI substrate was 50 μm thick, and the silver paste was 15 μm ± 2 μm thick.

[0149] I. Mechanical Performance Testing

[0150] Mechanical properties include adhesion test, flexural strength test and hardness test. The test results are shown in Table 1.

[0151] Adhesion is tested using a cross-cut adhesion test. After pulling with 3M 610 tape, the peeling level is evaluated (0 is the best, 5 is the worst).

[0152] The bending resistance test was conducted using a dynamic bending tester. The PI substrate with silver paste conductors was bent 180° repeatedly with a bending radius of R=3mm. The resistance change was monitored in real time, and the number of bends when the resistance change exceeded 10% was recorded.

[0153] Hardness was tested using a pencil hardness tester according to standard number ASTM D3363.

[0154] II. Conductivity Test

[0155] The sheet resistance of the cured silver paste conductors was measured using a four-probe tester. The results are shown in Table 1.

[0156] Table 1: Test results of mechanical properties and electrical conductivity

[0157]

[0158]

[0159] As shown in Table 1, the weldable low-temperature silver paste samples of this invention all exhibit excellent comprehensive performance. Among them, weldable low-temperature silver paste sample 1 shows the most outstanding performance, with the best adhesion grade of 0, a bending resistance exceeding 10,000 cycles, and maintaining low sheet resistance and high hardness. Weldable low-temperature silver paste control 1, due to its brittle and extremely poor flexibility in its resin system, breaks after less than 100 bending cycles and also exhibits extremely poor adhesion, failing to meet application requirements. This demonstrates the decisive role of the specific resin system of this invention in determining mechanical properties. The conductivity and mechanical properties of weldable low-temperature silver paste control 2 are close to those of sample 1, indicating that small-particle-size alloy powder has little impact on basic properties when well dispersed. Weldable low-temperature silver paste control 3 shows a significantly increased sheet resistance and decreased bending resistance, indicating that modified nano-antimony tin oxide plays an important role in reducing contact resistance, improving conductivity, and enhancing the mechanical strength of the system, exhibiting a synergistic effect with modified carbon nanotubes. The addition of a dispersant to the solderable low-temperature silver paste control 4 resulted in a significant increase in sheet resistance, proving that the addition of a dispersant under this invention actually hindered the direct contact of the conductive filler and degraded the conductivity. It can be seen that this invention achieves stable dispersion of nanofillers through material modification rather than the addition of a dispersant.

[0160] III. Welding Performance Testing

[0161] On the silver-soldered pads, Sn42Bi58 low-temperature solder paste and Mini LED chips were mounted using a standard SMT reflow soldering process (peak temperature 175℃). One hundred solder joints were observed, and the soldering yield (i.e., the percentage of solder joints without cold solder joints, false solder joints, or tombstoning) was calculated. Twenty soldered LED chips were selected using a push tester to test their shear strength, and the failure modes were recorded. The failure modes were categorized into three types: internal solder joint fracture, silver paste interface peeling, and a mixed mode of both. The results are shown in Table 2.

[0162] Table 2: Welding performance test results

[0163] Sample to be tested Welding yield (%) Shear strength (N) Failure Mode Solderable low-temperature silver paste sample 1 100 8.5 Internal fracture of solder joint Sample 2 of solderable low-temperature silver paste 99.5 7.8 Internal fracture of solder joint 3 samples of solderable low-temperature silver paste 98.0 6.5 Hybrid mode Solderable low-temperature silver paste reference standard 1 85.0 3.2 Silver paste interface stripping Solderable low-temperature silver paste reference standard 2 88.0 3.8 Silver paste interface stripping Weldable Low-Temperature Silver Paste Reference Standard 3 99.0 7.0 Internal fracture of solder joint Solderable low-temperature silver paste reference standard 4 75.0 2.5 Silver paste interface stripping

[0164] As shown in Table 2, the solderable low-temperature silver paste samples of this invention exhibit superior solderability, high welding yield, and high solder joint strength. Furthermore, the failure mode is predominantly internal fracture of the solder joint, indicating that the weld joint strength is far higher than the bonding strength between the silver paste and the pad, resulting in extremely high welding reliability. Solderable low-temperature silver paste control 1, due to its poorest adhesion, experienced stress during welding causing the silver paste layer to peel off from the substrate, resulting in extremely low welding yield and strength. In solderable low-temperature silver paste control 2, the alloy powder with excessively small particle size has a large specific surface area, leading to severe surface oxidation and easy agglomeration during curing, resulting in loss of activation properties and an inability to form an effective metallurgical bond with the solder. This is mainly manifested as silver paste interface peeling, severely deteriorating welding performance. Solderable low-temperature silver paste control 3 shows acceptable welding performance, proving that the weldability is mainly provided by the alloy powder; however, its strength is slightly lower, possibly due to poor conductivity and slightly uneven heating. The dispersant in the solderable low-temperature silver paste control 4 migrates to the surface of the silver paste, contaminating the solder pads and resulting in extremely poor solder wettability. The soldering yield and strength are both the worst, which once again proves that adding dispersant has a negative impact on this invention.

[0165] IV. Application Performance of Backlight Module

[0166] The backlight module samples prepared in Examples 4 to 6 were tested as follows:

[0167] 1. Temperature cycling test: 500 cycles were performed at temperatures ranging from -55℃ to 125℃. After the test, all samples from Examples 4 to 6 showed no dead or dimmed LEDs, the lighting yield remained at 100%, and no obvious cracks were observed at the solder joint interface.

[0168] 2. High temperature and high humidity aging test: The samples were tested for 1000 hours under 85℃ / 85%RH conditions. During the test, all samples from Examples 4 to 6 showed no decrease in brightness and stable chromaticity coordinates, demonstrating that the circuits and solder joints constructed with this silver paste have extremely high long-term reliability.

[0169] In summary, the solderable low-temperature silver paste samples prepared by this invention, especially sample 1, successfully combine excellent mechanical properties, outstanding electrical conductivity, and ultra-high soldering reliability, with overall performance far superior to various comparative examples.

[0170] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A flexible printed circuit board for notebook computers based on solderable low-temperature silver paste, comprising a flexible insulating substrate and a conductor pattern disposed on the substrate, characterized in that, The conductor pattern includes a main circuit pattern formed of rolled copper and an auxiliary functional structure formed in a local area of ​​the main circuit pattern by solderable low-temperature silver paste; the auxiliary functional structure includes at least one of a local repair area, a jumper area, and a pad area. The curing temperature of the solderable low-temperature silver paste is 130℃~145℃; by mass parts, the solderable low-temperature silver paste comprises 55.1 parts~75 parts conductive filler, 10 parts~20 parts polymer resin system, 20 parts~35 parts ester solvent, 3 parts~8 parts curing agent, 1 part~3 parts silane coupling agent, 0.5 parts~2 parts polyamide wax thixotropic agent, 0.2 parts~0.5 parts polysiloxane defoamer, 0.5 parts~2 parts modified carbon nanotubes and 0.5 parts~2 parts modified antimony tin oxide powder; The conductive filler comprises flake silver powder with a D50 range of 2.0μm to 5.0μm, spherical silver powder with a D50 range of 0.5μm to 0.8μm, and low-temperature alloy powder, wherein the low-temperature alloy powder has a D50 range of 12μm to 15μm. The polymer resin system comprises cashew nut shell epoxy resin, hydrogenated bisphenol A epoxy resin, and carboxyl-terminated liquid nitrile rubber in a mass ratio of 1:(0.8~1.2):(0.3~0.6); the cashew nut shell epoxy resin has an epoxy value of 0.45eq / 100g~0.55eq / 100g and a viscosity of 10000mPa·s~20000mPa·s at 25℃; the carboxyl-terminated liquid nitrile rubber has a carboxyl group mass fraction of 0.4%~0.6% and a number average molecular weight of 3000Da~5000Da; The preparation process of the modified antimony tin oxide powder, by mass parts, is as follows: B1. Disperse 10 parts of antimony tin oxide powder with an average particle size of 30nm to 70nm in 100 parts to 120 parts of anhydrous ethanol, and sonicate at 200W to 40W for 20min to 40min to obtain a suspension. B2. Add 1 to 2 parts of KH-560 and 0.2 to 0.8 parts of acetic acid to the suspension as a catalyst, and stir the reaction at 55°C to 65°C for 3 to 5 hours. B3. After the reaction is completed, the mixture is centrifuged, washed, dried and ground, and then passed through a 500-800 mesh sieve to obtain the modified antimony tin oxide powder.

2. The flexible printed circuit board for notebook computers according to claim 1, characterized in that, The mass ratio of flake silver powder, spherical silver powder, and low-temperature alloy powder in the conductive filler is (1.5–2.5):1:(0.2–0.5); the tap density of the flake silver powder is ≥4.0 g / cm³. 3 The low-temperature alloy powder is Sn42Bi58; the specific surface area of ​​the spherical silver powder is 1.0 m². 2 / g~2.5m 2 / g.

3. The flexible printed circuit board for notebook computers according to claim 1, characterized in that, The curing agent is a polyether polyamine curing agent and an imidazole accelerator in a mass ratio of (5-7):

1. The imidazole accelerator is selected from any one of 2-methylimidazole, 2-ethyl-4-methylimidazole or 1-cyanoethyl-2-phenylimidazole. The polyether polyamine curing agent is selected from linear polyether diamine.

4. The flexible printed circuit board for notebook computers according to claim 1, characterized in that, The silane coupling agent is γ-glycidoxypropyltrimethoxysilane; the polysiloxane defoamer is a non-silicone defoamer containing defoaming polysiloxane; the ester solvent is selected from any one of diethylene glycol butyl ether acetate, ethylene glycol ethyl ether acetate, or butyl butyrate.

5. The flexible printed circuit board for notebook computers according to claim 1, characterized in that, The polyamide wax thixotropic agent is a polyamide wax formed by the condensation of plant fatty acids, dimer fatty acids and ethylenediamine. Before use, the polyamide wax thixotropic agent needs to be activated. The specific operation of the activation treatment is as follows: add the polyamide wax to a mixed solvent of isopropanol and N-methylpyrrolidone with a volume ratio of 1:1.5 to 2.0, add aminopropanol, control the activation temperature at 40℃ to 50℃, the stirring speed at 100 r / min to 150 r / min, and activate for 15 min to 30 min; wherein, the mass ratio of polyamide wax, mixed solvent and aminopropanol is 1:(5 to 8):(0.05 to 0.1).

6. The flexible printed circuit board for notebook computers according to claim 1, characterized in that, The preparation process of the modified carbon nanotubes, by mass parts, is as follows: A1. Acidification treatment: Add 15 parts of carbon nanotubes to a mixed acid consisting of 280-320 parts of concentrated nitric acid and 100-150 parts of concentrated sulfuric acid, add 1%-5% of ferric nitrate nonahydrate by mass of carbon nanotubes, reflux at 105℃-115℃ for 4-8 hours, cool and filter, wash with deionized water until neutral, dry to obtain carboxylated carbon nanotubes to be cleaned. A2. Cleaning of carboxylated carbon nanotubes: The obtained carboxylated carbon nanotubes to be cleaned are dispersed in a nitric acid solution with a concentration of 0.1 mol / L to 0.5 mol / L, and ultrasonically treated at 200 W to 40 W at 40℃ to 60℃ for 20 min to 40 min; filtered, washed with deionized water until the conductivity of the filtrate decreases by <10 μS / cm, and dried to obtain carboxylated carbon nanotubes; A3. Silanization modification: Take 10 parts of the carboxylated carbon nanotubes described above and disperse them in a mixed solution of 120 to 180 parts of ethanol and water, with a volume ratio of ethanol to water of 1:(0.8 to 1.2). Add 1 to 3 parts of KH-560 and react with ultrasonic stirring at 68℃ to 72℃ for 5 to 7 hours. After the reaction is completed, filter, wash, and dry to obtain silanized modified carbon nanotubes. The ultrasonic power is 200W to 400W, and the stirring speed during the ultrasonic process is 300r / min to 500r / min. A4. Supercritical treatment: Take 5 parts of the silanized modified carbon nanotubes, 120-180 parts of deionized water, and 13-18 parts of cocamidopropyl dimethylamine acetone and add them to a supercritical reactor. After sealing, introduce carbon dioxide to a pressure of 28-32 MPa and react at a temperature of 73-78°C for 5-7 hours. After depressurization, add 3-8 parts of dodecyl dimethyl benzyl ammonium chloride and inject carbon dioxide to a pressure of 48-52 MPa. Stir at a speed of 200-400 r / min for 3-5 hours. A5. After depressurization, the modified carbon nanotubes are separated, washed, and dried to obtain the modified carbon nanotubes.

7. The flexible printed circuit board for notebook computers according to claim 1, characterized in that, The method for preparing the solderable low-temperature silver paste is as follows: S1. Add ester solvent to the reaction vessel, then add polymer resin system, stir at 60℃~80℃ until the resin dissolves, add silane coupling agent and polysiloxane defoamer, cool to room temperature, add curing agent, keep the solution temperature at 22℃~30℃, stir until all phases are completely dissolved and mixed to obtain carrier solution. S2. Add polyamide wax thixotropic agent to the carrier solution and stir at room temperature to obtain mixed solution A; S3. Add low-temperature alloy powder to mixed solution A and stir at room temperature to obtain mixed solution B; S4. Add the flake silver powder and spherical silver powder to the mixed solution B, and stir at room temperature to obtain the mixed solution C; S5. Add the modified carbon nanotubes and modified antimony tin oxide powder to the mixed solution C, stir and mix, and control the stirring temperature to not exceed 30℃ to obtain the mixed solution D; S6. Transfer the mixed solution D to a three-roll mill. First, adjust the gap between the fast roller and the middle roller to 65μm-75μm and the gap between the middle roller and the slow roller to 25μm-35μm, and grind for 1-2 passes. Then, adjust the gap between the fast roller and the middle roller to 35μm-45μm and the gap between the middle roller and the slow roller to 5-15μm, and grind for another 1-2 passes. Grind for a total of 2-4 passes to obtain the ground silver paste. S7. Transfer the ground silver paste to a vacuum stirring vessel and stir and mix it under a vacuum of ≤-0.095MPa. After stirring, encapsulate the silver paste to obtain the solderable low-temperature silver paste.

8. A backlight module based on solderable low-temperature silver paste, comprising a notebook flexible printed circuit board based on solderable low-temperature silver paste as described in any one of claims 1 to 7, and a Mini LED chip soldered to a conductor pattern on the notebook flexible printed circuit board by low-temperature solder; the Mini LED chip is soldered to a pad area formed by the solderable low-temperature silver paste in the conductor pattern.